An existence result for (p, q)-Laplace equations involving sandwich-type and critical growth. (January 2021) - Ho, Ky; Sim, Inbo
Abstract: We investigate the existence of a nontrivial nonnegative solution to ( p, q ) -Laplace equations involving two nonlinear terms, one grows as s with q < s < p and the other possibly has critical growth. This interesting case cannot be appeared in single m -Laplace equations and has not been studied under even the subcritical growth. Our argument is based on the concentration–compactness principle by P.L. Lions and the Ekeland variational principle.